PONDOK PESANTREN DALAM PENGEMBANGAN PENDIDIKAN KEISLAMAN - Sumarto Sumarto (Universitas Muhammadiyah Metro, 2018)
Historically, Islamic boarding schools were Islamic educational institutions developed by Indonesian people. Because actually pesantren is a cultural product of Indonesian people who are fully aware of the importance of education for indigenous people who grow naturally. Regardless of where the tradition and system is adopted, it will not affect unique patterns and have taken root and lived in the community. The pattern of life in pesantren is formed naturally through the process of planting values and developing the process of influencing influence with society. Islamic boarding schools always experience dynamics that never stop, in line with the social changes that occur.In the pesantren management system, the existence of a vision and mission occupies an important position. The vision must be formulated earlier and then set forth in the mission, namely programs and activities to realize the vision, and furthermore is to compile an action program in a mature and flexible plan to be implemented in a certain period of time in stages. The vision and mission of Islamic education which is the hope, ideals, and goals of Islamic education, are basically built from Islamic values and the results of analysis of the existence of Islamic education.Islamic boarding schools should be the center of Islamic education development, because; Islamic Boarding School is a center of religious education, which combines general and religious education, becomes a fortress for scientific balancers which are increasingly rapid by the influence of globalization, the development of science and knowledge is unstoppable, so Islamic boarding schools present as a fortress to provide boundaries that are in accordance with Islamization. This paper explains how Islamic boarding schools should be in developing Islamic education, preserving and preserving Islamic scholarship as a practice and practice.